Morpho-molecular identification and myco-chemical profiling of endophytic fungi isolated from Psidium Guajava - Zaima, Faizah (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2022.